2022
DOI: 10.1111/aogs.14348
|View full text |Cite
|
Sign up to set email alerts
|

Uterine conservative–resective surgery for selected placenta accreta spectrum cases: Surgical–vascular control methods

Abstract: Introduction:The incidence of placenta accreta spectrum (PAS) has increased, but the optimal management and the optimal way to achieve vascular control are still controversial. This study aims to compare maternal outcomes between different methods of vascular control in surgical PAS management. Material and methods: A retrospective cohort study on consecutive cases diagnosed with PAS between 2013 and 2020 in single tertiary hospital. The final diagnosis of PAS was made following preoperative ultrasound and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 41 publications
(117 reference statements)
1
22
0
1
Order By: Relevance
“…This retrospective descriptive study included women with histologically confirmed PAS 11 treated from 2016 to 2021 in 2 PAS centers in LMICs: the Dr. Soetomo General Academic Teaching Hospital, Universitas Airlangga, Surabaya, Indonesia (SGATH), and Clínica de Acretismo Placentario, Fundación Valle del Lili, Cali, Colombia (CAP). 5 , 12 A resource-poor setting was defined as a hospital with a low level of maternal healthcare, in which it is possible to manage uncomplicated pregnancies, and detect, stabilize, and initiate management of unanticipated maternal–fetal problems and high-risk antepartum, intrapartum, or postpartum conditions, but not complex maternal–fetal conditions. 13 We included all women with prenatally undiagnosed PAS who underwent CD in a resource-poor hospital and who, after initial management in that hospital, were transferred to the PAS center.…”
Section: Methodsmentioning
confidence: 99%
“…This retrospective descriptive study included women with histologically confirmed PAS 11 treated from 2016 to 2021 in 2 PAS centers in LMICs: the Dr. Soetomo General Academic Teaching Hospital, Universitas Airlangga, Surabaya, Indonesia (SGATH), and Clínica de Acretismo Placentario, Fundación Valle del Lili, Cali, Colombia (CAP). 5 , 12 A resource-poor setting was defined as a hospital with a low level of maternal healthcare, in which it is possible to manage uncomplicated pregnancies, and detect, stabilize, and initiate management of unanticipated maternal–fetal problems and high-risk antepartum, intrapartum, or postpartum conditions, but not complex maternal–fetal conditions. 13 We included all women with prenatally undiagnosed PAS who underwent CD in a resource-poor hospital and who, after initial management in that hospital, were transferred to the PAS center.…”
Section: Methodsmentioning
confidence: 99%
“…Total operation time was ranging from 2 to 3 hours. In this study, blood loss amount in almost cases was reduced to less than 1,500 mL, the level of 1,500 mL can be considered as "cut-off point" in conservative surgery [16]. In this study, intraoperative blood loss was less than 1,500ml in 51 of 65 women, however, the patients needed to blood transfusion in 57 cases due to pre-and postoperative anemia.…”
Section: Stage 1: Filter Database On the Computer At The Operative De...mentioning
confidence: 76%
“…Therefore, besides the development of imaging technology in diagnosing early PASD, the fundamental role of surgery is also extremely important [14]. The advanced trend in PASD management is conservative surgery and preventing catastrophic blood loss [15,16]. In fact, we have many reliable methods to prevent massive postpartum haemorrhage (PPH) and approaching conservative treatment such as internal iliac artery ligation, leaving the placenta completely or partially in situ with or without selective arterial embolization, the stepwise caesarean delivery Nevertheless, some complications have been reported regarding of above-mentioned methods if leaving the placenta in situ, such as severe haemorrhage, septic shock, renal failure, electrolyte imbalance, and pulmonary embolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-surgery partial myometrial resection and reconstruction of the uterus is a treatment approach in some areas of the world. [88][89][90] This strategy involves en bloc resection of the placenta and attached myometrium in well-selected cases, followed by repair and reconstruction of the remaining uterus and cervix. 91 This strategy is typically performed during the same surgery as cesarean delivery.…”
Section: Partial Myometrial Resection and Uterine Reconstructionmentioning
confidence: 99%